Filling in the Gap: A Hermeneutic Phenomenological Study of the Lived Experiences of Agricultural Change Agents in Northern Haiti - Priscilla Zelaya; Amy Harder; T Grady Roberts (Journal of International Agricultural and Extension Education, 2018)
In order to better understand the lived experiences of change agents in the North Department of Haiti, a hermeneutical phenomenological study was conducted. Change agents must work against a variety of barriers in order to help influence change within their spheres of influence in rural Haiti. The change agent experience in this study is collaborative, mutually benefitting, deeply cultural, and built out of necessity. Change agents in this study have found that by working together, they are able to fill in the gaps left by unequal distributions of resources within their communities such as tools, money, advisory services, or even basic agricultural knowledge. Despite holes within the agricultural support services in their areas, the change agents have mobilized community members to work together to move their communities forward. Understanding the lived experiences of change agents will help inform ongoing and future agricultural development efforts in the North Department of Haiti.
Keywords: community-based organizations; perspectives; capacity-building; sustainable development